Divorce and remarriage in the Bible : the social and literary context - Instone-Brewer, David (William B. Eerdmans Pub. Co, 2002)
Abstract: "By looking closely at the biblical texts on divorce and remarriage in light of the first century Jewish and Greco-Roman world, this book shows that the original audience of the New Testament heard these teachings differently. Through a careful exploration of the background literature of the Old Testament, the ancient Near East, and especially ancient Judaism, David Instone Brewer constructs a biblical view of divorce and remarriage that is wider in scope than present-day readings." "Among the important findings of the book are that both Jesus and Paul condemned divorce without valid grounds and discouraged divorce even for valid grounds; that both Jesus and Paul affirmed the Old Testament grounds for divorce, that the Old Testament allowed divorce for adultery and for neglect or abuse, and that both Jesus and Paul condemned remarriage after an invalid divorce but not after a valid divorce. Instone-Brewer shows that these principles are not only different from the traditional church interpretation of the New Testament but also directly relevant to modern relationships."